Implementasi kurikulum merdeka skema mandiri belajar pada lembaga pendidikan anak usia dini - Astutik, Anita Puji; Khoirinindyah , Safitri (PERDIKAN (Journal of Community Engagement), 2024)
Responding to the Ministry of Education and Culture's policy regarding an independent curriculum, several schools are not registered with the driving school but have not yet received encouragement. This causes an uneven understanding of the independent curriculum. Supposedly, schools that have registered in the driving school program can contact other educational units. This activity aims to overcome the lack of understanding of teachers who implement the independent learning scheme regarding the Merdeka curriculum. This is the focus of the problem, namely the limited number of Early Childhood Education Institutions in Sidoarjo district that are registered with driving schools, the lack of intensity of instruction at non-driving schools, and the lack of information in Sidoarjo district regarding the Merdeka curriculum. A solution to the partners' problems is obtained by providing teachers with an understanding of the Merdeka curriculum through workshop activities. The implementation method in this program. First, it begins with coordination and interviews regarding the implementation of the Independent Curriculum in Sidoarjo district. Coordinate with partners and research members, including lecturers and students, to create a work plan. The result of this activity is an increase in understanding about the implementation of the independent curriculum, especially in schools that take the independent learning scheme through the ability to develop teaching tools. The service team monitors and evaluates the results of the workshops that have been carried out to become the basis for implementing standard controls and as a basis for implementing continuous improvements. The conclusion from this activity is that this training has had a big impact on understanding the concept of an independent curriculum, even though the level of understanding varies between schools. As a follow-up, the team monitors continuously. [Menyikapi kebijakan Kemendikbud tentang kurikulum merdeka, ada beberapa sekolah yang tidak terdaftar di sekolah penggerak, namun belum mendapatkan pengimbasan. Hal ini menyebabkan tidak meratanya pemahaman tentang kurikulum merdeka. Seharusnya, sekolah yang telah terdaftar dalam program sekolah penggerak dapat melaksanakan pengimbasan ke satuan Pendidikan lain. Tujuan dari kegiatan ini untuk mengatasi kurangnya pemahaman guru yang menerapkan skema mandiri belajar tentang kurikulum Merdeka. Hal inilah yang menjadi fokus permasalahan yaitu terbatasnya Lembaga Pendidikan Anak Usia Dini di kabupaten Sidoarjo yang terdaftar pada sekolah penggerak, kurangnya intensitas pengimbasan pada sekolah-sekolah non sekolah penggerak, serta minimnya kabupaten Sidoarjo tentang kurikulum Merdeka. Sehingga diperoleh solusi dari permasalahan mitra, yaitu memberikan pemahaman guru tentang kurikulum Merdeka melalui kegiatan workshop. Metode pelaksanaan dalam program ini, pertama, diawali dengan berkoordinasi dan interview mengenai implementasi Kurikulum Merdeka di kabupaten Sidoarjo. Serta mengadakan koordinasi dengan mitra serta anggota peneliti yang terdiri dari dosen dan mahasiswa untuk membuat workplan. Hasil kegiatan ini adalah adanya peningkatan pemahamannya tentang implementasi kurikulum merdeka khususnya pada sekolah yang mengambil skema mandiri belajar melalui kemampua Menyusun perangkat ajar. Tim pengabdi melakukan monitoring dan evaluasi terhadap hasil workshop yang telah dilaksanakan untuk menjadi dasar dilaksanakannya pengendalian standar serta menjadi dasar dilaksanakannya perbaikan berkelanjutan. Kesimpulan dari kegiatan ini adalah pelatihan ini sangat berdampak dalam pemahaman konsep kurikulum merdeka, meskipun tingkat pemahaman antar sekolah berbeda-beda. Sebagai tindak lanjut, tim memantau secara berkelanjutan sampai hasil pemahaman tentang kurikulum merdeka maksimal dan diimplementasikan dengan baik.]